The Role Of Mandarin In Business Communication In Chinese Multinational Companies: A Literature Review - Alvionita Alindra, Devi; Halim, Norica; Evelyn, Jesslyn; Putri Paradida, Yulia (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This study aims to examine the strategic role of the Mandarin language in business communication within Chinese multinational companies through a literature review approach. As China's global economic influence continues to rise, proficiency in Mandarin has become a valuable asset in establishing effective professional relationships. Mandarin functions not only as a communication tool but also as a representation of Chinese cultural values such as hierarchy and respect, which are essential in business interactions. This research is descriptive qualitative research with literature review approaches. Data collection techniques in this research are carried out through literature studies, and The findings indicate that the use of Mandarin enhances corporate credibility, accelerates decision-making, and improves operational efficiency. However, its implementation faces several challenges, including a limited number of Mandarin-proficient human resources, differences in communication styles, and the linguistic complexity of the language. To address these challenges, strategies such as language and cultural training, recruitment of bilingual staff, utilization of translation technology, and cultural liaison approaches are identified as effective solutions. This study emphasizes that Mandarin is no longer merely an added value but a strategic necessity for multinational companies aiming to compete in the Chinese and broader Asian markets.